A year full of stories - McAllister, Angela (Frances Lincoln Children's Books, 2016)
This treasury of 52 stories collects a re-telling of myths, fairy tales and legends from around the world, with a story for every week of the year. The book is broken into 12 chapters, for each of the 12 months of the year, and throughout, stories are matched to internationally celebrated dates, including Valentines Day and the International Day of Friendship, as well as seasonal events and festivals.--Publisher
Vom Cover: 52 folktales and legends from around the world
Keywords: Folklore / Juvenile literature; Legends; Tales; Folklore; Anthologie; Kinderbuch